The trend of the distribution of ectopic pregnancy sites and the clinical characteristics of caesarean scar pregnancy - Panpan Tang; Xiaomao Li; Wenwei Li; Yunhui Li; Yu Zhang; Yuebo Yang (BMC, 2022)
Plain language summary Ectopic pregnancy occurs when a fertilized ovum implants outside the endometrium of the uterine cavity, which is a life-threatening occurrence and is an important cause of pregnancy-related mortality. With the increase in pelvic and intrauterine operations, the distribution of ectopic sites has been changing, but the variation has been insufficiently studied. To investigate the distribution of ectopic sites and its variation trend in depth, we collected the data of 3915 ectopic pregnancy cases from the third affiliated hospital of Sun Yat-Sen University. Through χ2 test for trend, the ratio of caesarean scar pregnancy to ectopic pregnancy showed an upward trend (P = 0.005). From 2012 to 2015 and 2016-2019, the ratio of caesarean scar pregnancy to ectopic pregnancy increased from 5.74 to 11.81% (P < 0.001). As the increasing of the ratio of caesarean scar pregnancy to ectopic pregnancy, the clinical characteristics of caesarean scar pregnancy was analysed. A total of 72.78% (246/338) caesarean scar pregnancy patients had one caesarean delivery, 25.15% (85/338) had two caesarean deliveries, and 2.07% (7/338) had three caesarean deliveries. A total of 80.18% (271/338) had aborted before. The most common clinical manifestations were amenorrhea (98.52%), abdominal pain (25.74%) and vaginal bleeding (67.76%), the most common sign was uterine enlargement (46.75%). As the ratio of caesarean scar pregnancy increases, the caesarean delivery rate should be decreased to decrease the morbidity of caesarean scar pregnancy.